Epics and Science: A Research Portfolio (Parts 1-4 + Festival Essays) (Global Journal of Human-Social Science, 2025)
This research portfolio, Epics and Science: Mahakavya Parts 1â€“4, examines the Mahabharata, Ramayana, Puranic texts, and Nepali festival traditions as repositories of encoded scientific knowledge. Rather than treating them as mythological or purely devotional, the work analyzes their narratives through the lens of modern biology, genetics, neuroscience, energy science, and sociology. Part 1 explores reproductive technologies, genetic manipulation, test-tube births, and surveillance concepts in the Mahabharata and Ramayana, showing their parallels with sperm donation, IVF, cloning, and telecommunication. Part 2 reinterprets the Samudra Manthan as a metaphor for energy generation, chemical synthesis, and early biochemical experimentation, alongside Dakshaâ€™s yajna (organ transplantation) and Jalandhar (cloning). Part 3 investigates physiological experiments encoded in Lakshmanâ€™s 14 years of wakefulness, Kumbhakarnaâ€™s failed sleep-cycle experiment, and ascetic fasting practices, connecting them with modern chronobiology and metabolic science. Part 4 analyzes Anusuyaâ€™s transformation, Ashtavakraâ€™s prenatal cognition, and the symbolism of lunar energy in Shiva traditions. It highlights â€œbrain incarnationâ€ â€” the continuity of consciousness beyond the physical body â€” as the ultimate hypothesis, bridging ancient spiritual inquiry with modern neuroscience. The portfolio also extends into Nepali cultural practices such as Teej, Rishi Panchami, and Janai Purnima, demonstrating how festivals preserved survival codes, nutrition science, and socio-biological balance across centuries. Overall, this interdisciplinary work proposes that epics and festivals were not primitive myths, but deliberate vehicles of research â€” embedding scientific experimentation within symbolic narratives to protect, transmit, and inspire across generations. By decoding these texts, modern science may rediscover forgotten hypotheses and open new directions in consciousness studies, biology, and human survival.